Dimensions of need - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dimensions of need: an atlas of food and agriculture edited by Tony Loftas 1995 127pp ISBN 92 5 103737 X FAO, Viale delle Terme di Caracalla, 00100 Rome, ITALY